Main Features of Magnetospheric Dynamics in the Conditions of Pressure Balance - Stepanova, M (Elsevier Ltd, 2023)
We analyzed the applicability of a hydrodynamic approach to the analysis of large-scale magnetospheric dynamics in the conditions of quiet geomagnetic activity. The main parameter, determining the applicability of the ideal MHD, is the ratio between the Alfvén and plasma velocities. We obtained the 2D distribution of this parameter using data of the THEMIS mission at geocentric distances <20 RE, and showed that not only the ring current region can be described suggesting full pressure balance. The external part of the ring current, which is localized in the surrounding the Earth plasma ring and earlier considered as a plasma sheet continuation, can be regarded as a stress balance region as well. Azimuthal plasma pressure gradients in this region create a system of large-scale field-aligned currents. Their closing in the ionosphere generates a large-scale convection in the ionosphere and magnetosphere. The mechanism of the large-scale convection control due to “penetration” of large-scale solar wind magnetic field is discussed. We discuss the role of turbulent transport in the analysis of magnetospheric regions, in which high level of turbulence is observed simultaneously with large-scale stress balance. © 2022 Elsevier Ltd